Impact of an antidote vacancy on the electronic and transport properties of germanene nanoribbons: A first principles study. (March 2020) - Samipour, Azam; Dideban, Daryoosh; Heidari, Hadi
Abstract: In this article, we investigate the effect of various antidote defects on the electronic properties and current characteristics of an armchair Germanene nanoribbon (AGeNR) using density functional theory (DFT) and non-equilibrium Green's function (NEGF) method. The defected AGeNRs are introduced by setting antidote topologies in the pristine nanoribbons, resulting in antidote super-lattice of AGeNRs. It is found that new electronic properties appear due to the presence of defects. The obtained results indicate that bandgap of the defected AGeNRs can be increased or decreased in different cases. Moreover, the transport properties are analyzed based on the various defect locations in the AGeNR when the ribbon is utilized as the channel of a tunneling field effect transistor (TFET). Based on our results, it is found that the presence of antidote defects leads to reduction or increase in the current, drifting the Dirac point, and decreasing or increasing the minimum or off-state current. Highlights: First principles study is carried out to investigate impact of antidotes on transport properties of Germanene nanoribbons. Four topologies of antidotes are introduced and bandstructures are obtained and compared with the pristine case. The bandgap size and the carrier effective mass is extracted, analyzed and compared from the bandstructures. The transport properties are analyzed when defected ribbon is utilized as the channel of a tunneling field effect transistor. The impact of position of antidotes on the electronic properties is investigated both in lateral and transverse direction.